E-Commerce Berbasis Android Pada Man Creative - Saputri, Sheren Tasyana; Elliya Sestri; Diana Yusuf (Jurnal Teknologi Informasi (JUTECH), 2023)
The background of research is able to listed as How to design application Android based, How to implement the design of applications Creative Man, how to test applications based on Android Agile Scrum methods will be used to build this application. Scrum is a methode based on agile principles is focus on effective teamwork, incremental products, and iterating processes to achieve the end result. Scrum, according to Schwaber & Sutherland, is a framework that can handle complex and ever-changing problems. In addition, it is considered to have the ability to provide high-quality products that match the desires of innovative and productive users in MAN Creative's medium-sized business of building an sales system that can be accessed online rather than replacing it. The old system still using offline system. Plan of built new system hopefully can expand the market with android applications. Customers can easily get information about any product sold without having go to Man Creative store. With new online system, MAN Creative can easily provide information about any product, such as product name, price, etc. MAN Creative can be known by many people.. Analysis of sales transaction security issues. In order for more expeditions to be available in the future, couriers or expeditions must be present. In the process of product development, its appearance will be updated to provide more complete information, including new or additional types of products.